Custom-Made Alumina Ceramic Total Talar Prosthesis for Idiopathic Aseptic Necrosis of the Talus: Report of Two Cases. (29th May 2017) - Tonogai, Ichiro; Hamada, Daisuke; Yamasaki, Yuhei; Wada, Keizo; Takasago, Tomoya; Tsutsui, Takahiko; Goto, Tomohiro; Sairyo, Koichi
Abstract : Two women aged 65 years and 78 years presented to our center with idiopathic necrosis of the talus. In both cases, imaging examinations showed collapse and sclerotic changes of the talar body caused by the necrosis. Both women underwent resection and placement of a third-generation custom-made alumina ceramic total talar prosthesis. Immobilization of the ankle in a short-leg cast for 3 weeks was followed by early rehabilitation. One year and 6 months after surgery, both women were able to walk without pain. Their Japanese Society for Surgery of the Foot ankle-hindfoot scale scores improved from 22 and 29/100 points to 90 and 95/100 points, respectively. To the best of our knowledge, the successful treatments of these two rare cases of idiopathic necrosis of the talus are among only a few reported cases of using a third-generation alumina ceramic prosthesis.